WOMEN’S RIGHTS AND GENDER EQUALITY ISSUES IN ISLAMIC LAW IN INDONESIA: THE NEED TO RE-READ WOMEN’S STATUS IN THE ISLAMIC RELIGIOUS TEXTS - Alfitri, Alfitri (IAIN Samarinda, 2014)
Artikel ini adalah untuk membahas status perempuan dalam teks-teks agama Islam, terutama ayat-ayat Quran dan Hadis teks yang dianggap